Influenza Diagnosis with a Specific Emphasis on the M2e Antigen as a Diagnostic Tool - Budama-Kilinc, Yasemin; Cakir-Koc, Rabia (INTECH EUROPE, 2016)
The therapy, observation, inclusiveness, and preclusion of related diseases all influence the diagnosis of influenza. Particularly, the pandemic duration and diagnosis time for influenza are extremely important. After the appearance of symptoms, antiviral medication must be initiated within 48 h. Cell culture, real-time polymerase chain reaction (PCR), flow cytometry, direct and indirect immunofluorescence methods, and the quick diagnosis test are all valuable approaches for the diagnosis of influenza. Different instruments, different time durations for the results, and different specialists characterize all these approaches. Antigen selection is of critical importance with regard to the specificity and sensitivity of these methods, especially the serological and rapid diagnosis tests. M2e, the highly conserved external domain of the influenza A M2 protein, is a potential differential diagnostic marker for influenza virus infection. This chapter reviews the studies that use M2e as a diagnosis agent, and it illuminates the role and importance of M2e in the diagnosis of influenza.
Keywords: M2e; diagnosis; peptide; antigen; virus culture; rapid immunochromotographic test; serological test; ELISA; PCR; H5N1 AVIAN INFLUENZA; A-VIRUS; EXTRACELLULAR DOMAIN; ENZYME-IMMUNOASSAY; HEMAGGLUTINATION INHIBITION; COMPLEMENT-FIXATION; PANDEMIC INFLUENZA; ANTIBODY-RESPONSE; RAPID DETECTION; INFECTION; Immunology; Virology